2016
DOI: 10.1007/s00277-016-2885-6
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles from splenectomized β-thalassemia/HbE patients play roles on procoagulant activities with thrombotic potential

Abstract: Thromboembolic events including cerebral thrombosis, deep vein thrombosis, and pulmonary embolism are major complications in β-thalassemia. Damaged red blood cells and chronic platelet activation in splenectomized β-thalassemia/HbE patients were associated with increased microparticles (MPs) releases into blood circulation. MPs are small membrane vesicles, which play important roles on coagulation. However, the role of MP in thalassemia is poorly understood. In this study, the effects of splenectomized-MPs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Haematological analysis revealed that β-thalassaemia/HbE patients had an anaemia phenotype with increased numbers of platelets and MPs (annexin V+ MPs) as described in previous studies 13 15 . The number of MPs originating from platelets and RBCs of β-thalassaemia/HbE was higher than normal-MPs.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Haematological analysis revealed that β-thalassaemia/HbE patients had an anaemia phenotype with increased numbers of platelets and MPs (annexin V+ MPs) as described in previous studies 13 15 . The number of MPs originating from platelets and RBCs of β-thalassaemia/HbE was higher than normal-MPs.…”
Section: Resultssupporting
confidence: 72%
“…In this study, the amount of MPs (5 × 10 6 particles/mL) used was about three fold lower than the physiological number of MPs in circulation in normal subjects (1.6 × 10 7 particles/mL). However, the percentages of platelet activation in platelets from splenectomised patients treated with splenectomised-MPs at 10-fold lower to 100-fold higher than physiological levels were significantly increased when compared to platelets treated with normal-MPs, and in dose dependent manner 15 . HUVECs incubated with MPs obtained from sickle cell disease (SCD) patients at about 5-fold lower than physiological levels resulted in increased reactive oxygen species production and apoptosis when compared with that of normal controls.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…After splenectomy, blood cell counts and circulating MPs increase. This has been observed in patients with immune thrombocytopenia (Fontana et al, 2008; Sewify et al, 2013), β-thalassemia intermedia (β-TI) patients (Pattanapanyasat et al, 2007; Habib et al, 2008; Westerman et al, 2008; Klaihmon et al, 2017) and TDT patients; in the latter group, splenectomy has been associated with higher levels of MPs (Tantawy et al, 2013; Elsayh et al, 2014; Agouti et al, 2015) and increased procoagulant activity of platelet MPs (Agouti et al, 2015). However, there have been no studies characterizing EVs in thalassemic patients with hypersplenism.…”
Section: Introductionmentioning
confidence: 91%